Calculation of performance indicators for passenger transport based on telemetry information; Engineering Technology, Engineering Education and Engineering Management (ETEEEM 2014) - Yurchenko M. A. Marina Aleksandrovna; Kochegurova E. A. Elena Alekseevna; Fadeev A. S. Aleksandr Sergeevich; Piletskaya A. Yu. Anastasiya Yurjevna (2015, 2015)
Title screen